Coping styles and clinical factors in relation to quality of life among patients with schizophrenia - Mohd Badli M; Osman CB; Ainsah O (Penerbit UKM, 2008)
This is a cross sectional study examining quality of life in relation to coping styles among patients with Schizophrenia (N=92) in remission, from June 2002 to December 2002. Remission state is determined by Brief Psychiatric Rating Scale (BPRS). The psychiatric diagnosis was made by treating psychiatrist using the Clinical Interview Schedule for the DSM-IV Diagnosis. They are subsequently asked to complete demographic and clinical data questionnaire and followed by 36-item short-form health survey (SF-36) of the Medical Outcome Study (MOS) for the assessment of quality of life and the Coping Inventory for Stressful Situation (CISS). The QOL in term of overall mental health among patients with schizophrenia was significantly and positively associated with ethnic group (p<0.05), employment status, type of antipsychotic (p<0.05) and number of admission (p<0.05). Being Chinese and employed are associated with better QOL in term of overall mental health. The commonly used coping style among patients with Schizophrenia is the distraction component of avoidance-oriented coping. The task-oriented coping was significantly and positively correlated with quality of life in term of mental component. There was a negative correlation between the emotion-oriented coping and all the domain of the quality of life. In conclusion, better quality of life is positively correlated with taskoriented coping and inversely related with emotion-oriented coping